Drivers of the pre-season drought thresholds triggering earlier autumn foliar senescence in the Northern Hemisphere - Wenbo Yan; Jian Zhou; Honghong Lin; Jinyi Luo; Xingwu Duan; Ruidong Wu (Nature Communications)
Abstract Global warming can postpone the autumn date of foliar senescence (DFS). Nevertheless, warming-associated droughts may induce earlier DFS. However, pre-season drought thresholds triggering an earlier DFS (PDT-DFS) are not clearly established. Using site-level DFS data since 1951, satellite-derived DFS data for 1982‒2021, and drought indices, we construct a copula-based Bayesian framework to identify the PDT-DFS over the Northern Hemisphere (>30°N). A higher probability of droughts is associated with an earlier DFS. The DFS for the <10%, <20%, <30%, and <40% quantiles (a lower quantile indicates that DFS will occur earlier under the same drought conditions) results in PDT-DFS values of −2.59, −2.30, −1.80, and −1.63, respectively. The propagation thresholds from meteorological droughts to soil droughts determine the PDT-DFS. However, an increase in resilience and leaf area index hinders the sensitivity of an earlier DFS to droughts. In Sixth Coupled Model Inter comparison Project (CMIP6) simulations, the PDT-DFS increases significantly (p < 0.01) under most climatic scenarios in the future. This study provides extensive evidence for the increasing sensitivity of DFS to pre-season droughts and a basis for enhanced predictive responses to such droughts.